THE ROLE OF LIQUIDITY AND FINANCING RISK INFLUENCING PROFITABILITY OF SHARIA RURAL BANK IN INDONESIA - Ridwansyah; Andriani, Yulia; Wiraputra, Jhody (Journal of Management and Islamic Finance, 2025)
This study aims to analyze and prove empirically the effect of liquidity and financing risk, either partially or simultaneously, on profitability at Sharia Rural Banks (SRB) in Indonesia during the period 2021 to 2024. This study uses a quantitative approach with monthly secondary data sourced from the Islamic Banking statistical reports of the Financial Services Authority (OJK). Data analysis techniques used are descriptive statistics, classical assumption test, and hypothesis test. The test results showed that liquidity has a positive and significant effect on the profitability of SRB, which indicates that optimal liquidity management is crucial in achieving profits. In contrast, variable risk financing (NPF) was found to have no significant effect on SRB profitability, implying that SRB may have implemented effective risk mitigation strategies to mitigate the impact of NPF on net income. And simultaneously the liquidity and financing risk variables do not affect the profitability of the SRB in Indonesia. These findings provide practical implications for SRB management and regulators to focus strategies on balancing cash availability with productive financing allocation in order to achieve sustainable profitability.